Education to Prevent Early Marriage in Teenagers Using The Snake and Ladder Game - Ryaz, Faeza; Sari, Rati Purnama; Rahmawati, Lisa (proceedinginternational, 2024)
One of the social problems that exist in Indonesia is early marriage. In 2022, approximately 52 thousand cases of marriage dispensation summited to the religious courts. One of contribute factor is reproductive health education to teenagers. This research aims to increase teenagers' insight into the dangers of early marriage for reproductive health. Using the Snakes and Ladders game, this study used a one-group pre-post-test design to increase teenagers' knowledge about early marriage. The sample of this research was 29 teenagers aged 12-13 years. Data collection was carried out in May 2023. The level of knowledge was measured using a questionnaire and t-test. The results of the level of knowledge before and after showed an increase in teenagers' knowledge of the dangers of early marriage for reproductive health. After data analysis was carried out The results show a significant difference between before being given education and after being given education regarding the dangers of early marriage in teenagers. The use of the snakes and ladders game can be used as an alternative medium in providing reproductive health education to prevent early marriage.